2016
DOI: 10.1007/s10548-016-0531-1
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Brain Function and Gray Matter Regional Volumes Differ According to Exercise History: Evidence from Monozygotic Twins

Abstract: Associations between long-term physical activity and cortical function and brain structure are poorly known. Our aim was to assess whether brain functional and/or structural modulation associated with long-term physical activity is detectable using a discordant monozygotic male twin pair design. Nine monozygotic male twin pairs were carefully selected for an intrapair difference in their leisure-time physical activity of at least three years duration (mean age 34 ± 1 years). We registered somatosensory mismatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(58 reference statements)
1
5
0
1
Order By: Relevance
“…We identified a subpopulation of MZ twin pairs, where the co-twins differed in their past 3-year LTPA. As reported earlier (Rottensteiner et al 2015, 2016; Tarkka et al 2016; Hautasaari et al 2017), the LTPA discordance created diet-independent differences between active and inactive co-twins in cardiorespiratory fitness, intra-abdominal adiposity, glucose homeostasis, and brain morphology and function. In this study, we found no differences between the co-twins in their systemic energy metabolism at rest or during exercise.…”
Section: Discussionsupporting
confidence: 60%
“…We identified a subpopulation of MZ twin pairs, where the co-twins differed in their past 3-year LTPA. As reported earlier (Rottensteiner et al 2015, 2016; Tarkka et al 2016; Hautasaari et al 2017), the LTPA discordance created diet-independent differences between active and inactive co-twins in cardiorespiratory fitness, intra-abdominal adiposity, glucose homeostasis, and brain morphology and function. In this study, we found no differences between the co-twins in their systemic energy metabolism at rest or during exercise.…”
Section: Discussionsupporting
confidence: 60%
“…12 Additional comparisons showed differing automatic deviance-detection processes in brain regions involved with sensorimotor, visual, and memory functions in electrophysiological studies between the more and less active co-twins. 13,14 For summary of the main results, see Figure 2. More data on the findings are also available in nine PhD theses (see links to the texts in Appendix S1).…”
Section: Brain Structure and Functionsmentioning
confidence: 99%
“…Additional comparisons showed differing automatic deviance-detection processes in brain regions involved with sensorimotor, visual and memory functions in electrophysiological studies between the more and less active co-twins. 24,25 is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Brain Structure and Functionsmentioning
confidence: 99%
“…Additional comparisons showed differing automatic deviance-detection processes in brain regions involved with sensorimotor, visual and memory functions in electrophysiological studies between the more and less active co-twins. 24, 25…”
Section: Main Findings On the Mz Pairs Discordant For Ltpamentioning
confidence: 99%